Chloride ion concentrations during the compression of rocks to extract pore water. Issue 1 (2nd April 2015) - Nakata, K.; Hasegawa, T.; Higashihara, T.; Oyama, T.
Abstract: Pore water needs to be extracted from rocks with low permeabilities to allow the major ion concentrations in the pore water to be estimated. Compressing a rock is the most widely used method of extracting the pore water. However, ion concentrations have been found to change during compression in previous studies, and the mechanisms involved in such ion concentration changes have not yet been fully assessed. In this study, two natural rocks and four artificially prepared samples were compressed, and changes in the chloride ion (Cl − ) concentrations as the compression pressure increased were investigated. Mechanisms that could have caused the changes observed were then assessed. The Cl − concentrations in squeezed water decreased as the pressure increased if the sample contained a significant amount of smectite. The strong dependence of Cl − concentration on the amount of smectite indicated that smectite played an important role in decreasing the Cl − concentration. The dilution of the pore water with interlayer water from the smectite appeared to be the dominant mechanism involved in the decrease in Cl − concentration found in a Kunigel‐V1 sample, because dilution of the pore water with interlayer water quantitatively explained the decrease in the Cl − concentration. The filter effect caused by the anion exclusion effect did not appear to be a dominant mechanisms in our case. However, Cl − concentration decrease found in natural rocks could not be fully explained by dilution with interlayer water, so other mechanisms must be involved the phenomenon in natural rocks.